A report on the practice in industry training in fish preservation. - Martinez, Santiago A. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1959)
The Philippines is a fisheries country by nature, gifted with vast ocean in all its shore that abound in fish. However, our country is continuously importing fish and fishery products despite the abundance of this natural resource awaiting exploitation. During the peak season, some of the catches are wasted due to insufficient knowledge of fish preservation. The training of technical men power is therefore indispensable in order to diminish or entirely eliminate the wasting of all the aquatic products. Fish preservation is one course that is being offered in the college of fisheries. This course consist of fishing curing, the canning of fish and fishery products, the utilization of the by products of all aquatic products, and the freezing of fish and other foodstuff. Students taking fish preservation are prepared thoroughly with the different methods and principles of fish processing and are afforded four months practice on the job training to enable them to put into practice what they have learned in the classroom.
Keywords: Fish-Preservation.